Multifunctional Hydrogels Based on γ-Polyglutamic Acid/Polyethyleneimine for Hemostasis and Wound Healing - Li, Xiuyun; Han, Wenli; Zhang, Yilin; Tan, Dongmei; Cui, Min; Wang, Shige; Shi, Wenna (Biomaterials research, 2024)
Current hemostatic materials have many shortcomings, such as biotoxicity or poor degradability, and do not effectively promote wound healing after hemostasis. To address these limitations, a hemostasis-promoting wound-healing hydrogel, polyglutamic acid/polyethyleneimine/montmorillonite (PPM), comprising polyglutamic acid, 3,4-dihydroxybenzaldehyde-modified polyethyleneimine, and amino-modified montmorillonite (montmorillonite-NH 2 ) was constructed in this study. Due to the excellent water absorption abilities of γ-polyglutamic acid, the PPM and polyglutamic acid/polyethyleneimine hydrogels could rapidly absorb the blood and tissue fluid exuded from the wound to keep the wound clean and accelerate the blood coagulation. The homogeneous distribution of montmorillonite-NH 2 enhanced not only the mechanical properties of the hydrogel but also its hemostatic properties. In addition, the modification of polyethylenimine with 3,4-dihydroxybenzaldehyde provided anti-inflammatory effects and endorsed the wound healing. Cellular and blood safety experiments demonstrated the biocompatibility of the PPM hydrogel, and animal studies demonstrated that the PPM hydrogel effectively stopped bleeding and promoted wound healing. The concept design of clay-based hydrogel may create diverse opportunities for constructing hemostasis and wound-healing dressings.